Incorporating dissent in the renewal of Dublin's inner city : engagements between the local state and inner-city communities in Dublin's Liberties - Brudell, Paula (Trinity College (Dublin, Ireland). Department of Geography, 2011)
This research addresses a crucial silence in the Irish neoliberal discourse, the voices and struggles of working-class communities resident in those areas in which the state pursued its neoliberal urban-development agenda throughout a decade of intensive development in Dublin’s inner city. The research was prompted by the discrepancy between the official consensus surrounding the Irish state’s urban-renewal agenda and the more critical assessments emanating from communities in the targeted areas. The extent to which those experiences and critiques were obscured from public view raised questions about the manner in which the Irish state managed to proceed almost with impunity while pursuing a highly political urban-development policy resulting in far-reaching negative consequences for working-class residents. The research explores the manner in which such apparent harmony and political quiescence is to be comprehended, notably addressing the degree to which the Irish state largely succeeded in either incorporating or marginalising and negating criticism, dissent and opposition while simultaneously, throughout the property-development boom, presenting the interests of the property-development sector as synonymous with the public good.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin